PENGEMBANGAN MODUL BIMBINGAN KE ARAH PENERIMAAN DIRI MELALUI BIMBINGAN KELOMPOK SISWA SMKN TUTUR PASURUAN - Dessy Ameliani Sasika Putri (Jurnal Bimbingan dan Konseling Borneo, 2020)
Vocational students who are in their teens often have problems related to self-acceptance. the analysis conducted need assessment to students of class XI, it is known that students need information about self-acceptance in the form of guidance modules. Test performed by 2 expert BK. Prospective user test the products carried by 2 people vocational counselor. Data obtained from test experts and potential users test the product in the form of quantitative and qualitative data. Through the data collection techniques and grading scale acceptability of input / suggestions for improvements are written in pieces of advice available. The results of this research is the development of the guidance module toward self-acceptance SMK Negeri Tutur The oracle consists of four aspects, namely: (1) aspects of usability by expert 1 average of 3.00, a 4.00 second average; (2) aspects of the attractiveness by an average of 3.00 1, expert 2 average 3.30; (3) aspects of practicality by an average of 3.16 1, expert 2 average 3.83; (4) aspects of accuracy by an average of 3.00 1, an average of 3.75 2. It can be concluded that the products have been developed very useful, very practical, very precise and very attractive, have acceptability in terms of theoretical Suggestion module development guidance toward self-acceptance is to be used as the media in providing services in the field of personal-social BK to increase self-acceptance vocational students.